Competitive Advantage Analysis of Shipyard Companies in Indonesia - Resa Nurlaela Anwar; Danny Faturachman; Melani Quintania; Hermin Sirait; Rini Setiawati (International Journal of Marine Engineering Innovation and Research, 2020)
The development of the shipping and shipyard industries in Indonesia over the past ten years has been very slow. Some of the causes, including low productivity and capacity, are the main reasons for this industry's penetration. In addition, the weakening of the national economy as a result of the weakening of the global economy also affected the domestic shipping industry. The competitiveness of the shipping and shipyard industry is influenced by industrial competitiveness and national competitiveness, so that shipyard industry problems must be solved comprehensively, accompanied by strategic and systematic steps in order to be able to compete sustainably. This study aims to analyze the strategies used by several shipping companies and shipyard companies to be able to survive and compete to win and get through severe conditions. This study uses descriptive qualitative method, which is supported by semi-structured interview techniques to obtain the data used in determining the resource person, using a purposive sampling method. The data collected is then tested for validity by using the triangulation of data sources to process the data obtained in developing alternative strategies using SWOT analysis (Strength, Weakness, Opportunities, Threat) In addition to the combination of SWOT methods. The findings of the research results state that all companies carry out defensive strategies so that they are a company that still exists today.